Stałość i zmienność warsztatu pracy nauczyciela = Stability and changeability of the teacher`s tools and skills - Kabat, Małgorzata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents considerations on the stability and changeability of the conditions which modify individual predispositions and the teacher?s skills and tools. The teacher is influenced by his further and closer school environment which has impact on the alterations in his skills and tools created with the passage of time. Modifications in those skills and tools result from the teacher entering into next phases of professional development and from gaining richer experience. In each phase, there appear new educational tasks and challenges that require using various theoretical and practical solutions.
Keywords: stałość; zmienność; nauczyciele; warsztat pracy; stability; changeability; teacher; teacher`s tools and skills